Efektifitas Insektisida Berbahan Aktif Klorantraniliprol terhadap Larva Spodoptera frugiperda (JE Smith) - Willing Bagariang; Enie Tauruslina; Umi Kulsum; Tri Murniningtyas PL; Hadi Suyanto; Surono Surono; Nanar A Cahyana; Didah Mahmuda (Plant Protection Departement, Faculty of Agriculture, Universitas Andalas, 2020)
Fall armyworm or Spodoptera frugiperda (J.E Smith) is a significant economic pest of maize. S. frugiperda is reported for the first time to attack and damage the corn in Indonesia since 2019. The study was aimed to find the effectivity of chlorantraniliprole to control the larvae of S. frugiperda on maize. The study was divided into two steps, in the laboratory and the field. The laboratory treatment was application of chlorantraniliprole 2 cc/l, Metarhizium anisopliae (10? conidia/ml), and Beauveria bassiana (10? conidia/ml) that applied onto the leaf, larvae, and leaf + larvae with five replications for each treatment. The field test used three treatments i.e., chlorantraniliprole field, farmer field, and control with three replications for each treatment. The research showed that chlorantraniliprole at a dose of 2 cc/l had the highest mortality of S. frugiperda with 100% mortality on average during five days after application. However, the application of M. anisopliae and B. bassiana did not affect the mortality of S. frugiperda for 3 days after application. There was no difference in mortality when chlorantraniliprole applied onto leaf, larvae and leaf + larvae. Application of chlorantraniliprole in the field at a dose of 2 cc/l at 1, 3, and 5 weeks after planting was effective to control S. frugiperda on maize. Keywords: Chlorantraniliprole, entomopatogenic fungi, fall armywarm